Genetic analysis and selection of Bambara groundnut (Vigna subterranea [L.] Verdc.) landraces for high yield revealed by qualitative and quantitative traits - Khan, Md Mahmudul Hasan; Yusop, Mohd Rafii; Ramlee, Shairul Izan; Jusoh, Mashitah; Al Mamun, Abdullah (Nature Publishing Group, 2021)
As a crop for the new millennium Bambara groundnut (Vigna subterranea [L.] Verdc.) considered as leading legumes in the tropical regions due to its versatile advantages. The main intent of this study was to find out the high yielding potential genotypes and considering these genotypes to develop pure lines for commercial cultivation in Malaysia. Considering the 14 qualitative and 27 quantitative traits of fifteen landraces the variation and genetic parameters namely, variability, heritability, genetic advance, characters association, and cluster matrix were determined. ANOVA revealed significant variation for all the agronomic traits (except plant height). Among the accessions, highly significant differences (P ≤ 0.01) were found for almost all the traits excluding fifty percent flowering date, seed length, seed width. The 16 traits out of the 27 quantitative traits had a coefficient of variation (CV) ≥ 20%. A positive and intermediate to perfect highly significant association (r = 0.23 to 1.00; P < 0.00) was found between yield and its related traits. The trait dry seed weight per plant (g) had the highest GCV = 59.91% and PCV = 59.57% whereas the trait fresh pod weight (99.55%), dry seed weight (98.86%), and yield (98.10%) were highly heritable. The genetic advance recorded the highest for dry seed weight (122.01%) and lowest (3.97%) for plant height. To validate the genetic disparity, an unweighted pair-group produce with arithmetic mean (UPGMA), principal component analysis (PCA), heatmap, and H’-index was performed considering 27 quantitative traits. The constructed dendrogram showed five distinct groups of accessions. Genotypes G2, G3, and G9 from Group IV consider as promising lines which gave 70.05% higher mean yield compared to grand mean yield (1180 kg ha−1) with desirable traits. Group II had a maximum number of accessions while group III and group V had one of each. However, findings declared that the availability of genetic variance will be beneficial for this crop improvement through cross breeding as well as the plant breeders to prefer desirable traits in V. subterranea L. Verdc. for further breeding purposes.